2016
DOI: 10.1002/nvsm.1556
|View full text |Cite
|
Sign up to set email alerts
|

Tourism donations in sacred settings: an exploratory study of visitor donations in an English cathedral

Abstract: 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A charitable attitude can be regarded as a kind of baseline altruism, and people with this attitude would do things that are beneficial to random strangers ( Leider et al, 2009 ). We can find similar attitudes in tourists giving money at churches ( Gutic & Caie, 2016 ), runners running charity marathons ( Nettleton & Hardey, 2006 ), volunteer field rescuers ( Uriely et al, 2002 ), hotel consumers who choose green hotels to stay (L. Wang, Wong, & Narayanan Alagas, 2020 ). Teng et al (2013) proposed an amended model based on TPB through research on tourists visiting green hotels and found that altruism affects people's willingness to visit green hotels by influencing tourists' attitudes and perceived behavior control.…”
Section: Introductionmentioning
confidence: 91%
“…A charitable attitude can be regarded as a kind of baseline altruism, and people with this attitude would do things that are beneficial to random strangers ( Leider et al, 2009 ). We can find similar attitudes in tourists giving money at churches ( Gutic & Caie, 2016 ), runners running charity marathons ( Nettleton & Hardey, 2006 ), volunteer field rescuers ( Uriely et al, 2002 ), hotel consumers who choose green hotels to stay (L. Wang, Wong, & Narayanan Alagas, 2020 ). Teng et al (2013) proposed an amended model based on TPB through research on tourists visiting green hotels and found that altruism affects people's willingness to visit green hotels by influencing tourists' attitudes and perceived behavior control.…”
Section: Introductionmentioning
confidence: 91%